2005
DOI: 10.1128/jvi.79.14.9026-9037.2005
|View full text |Cite
|
Sign up to set email alerts
|

Low Human Immunodeficiency Virus Envelope Diversity Correlates with Low In Vitro Replication Capacity and Predicts Spontaneous Control of Plasma Viremia after Treatment Interruptions

Abstract: Genetic diversity of viral isolates in human immunodeficiency virus (HIV)-infected individuals variessubstantially. However, it remains unclear whether HIV-related disease progresses more rapidly in patients harboring virus swarms with low or high diversity and, in the same context, whether high or low diversity is required to induce potent humoral and cellular immune responses. To explore whether viral diversity predicts virologic control, we studied HIV-infected patients who received antiretroviral therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 103 publications
1
49
0
Order By: Relevance
“…The diversity of the viral quasispecies may be a key determinant of the development and maintenance of NAb against autologous virus (47). In a study of patients undergoing structured treatment interruption, lower diversity prior to treatment correlated with better autologous virus neutralization and better viral suppression after HAART interruption (25). The diversity of env sequences of plasma viruses from ES has not been previously characterized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of the viral quasispecies may be a key determinant of the development and maintenance of NAb against autologous virus (47). In a study of patients undergoing structured treatment interruption, lower diversity prior to treatment correlated with better autologous virus neutralization and better viral suppression after HAART interruption (25). The diversity of env sequences of plasma viruses from ES has not been previously characterized.…”
Section: Resultsmentioning
confidence: 99%
“…The HLA-B*57 allele is overrepresented in ES (37) and was present in seven of nine of the ES in this study. Low env diversity theoretically favors viral suppression by NAb in these subjects (25,56). Although the low levels of replication occurring in these patients may have limited viral diversification, low antigen levels may also have prevented the stimulation of a high-titer antibody response.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic differences in the PND region included amino acid substitutions, size variation, and changes in the numbers and locations of predicted N-linked glycosylation sites. Similar changes in HIV-1 env that mask immune epitopes have been associated with a loss of virus replicative fitness (8)(9)(10)(11), suggesting that resistance to bNAb may incur a cost in virus fitness. In the present study, we used growth competition and infectivity assays to determine if EIAV PND variants that differ in sensitivity to neutralization also differ in replicative capacity in vitro.…”
Section: Equine Infectious Anemia Virus (Eiav) Induces a Persistent Lmentioning
confidence: 98%
“…Limiting dilution to approximately one copy was performed on postinterruption plasma samples from patient 116 (based on real-time PCR viral loads) and yielded very similar sequences, indicating that PCR recombination might not have been a problem. Using a very similar molecular cloning approach for a comparable region of envelope, others found PCR misincorporation artifacts to be minimal (27). Furthermore, Jordan et al found no difference in population structure or genetic diversity between terminal dilution cloning and conventional cloning for 14 of 17 subjects studied, demonstrating both methods are suitable for the study of viral genomic diversity (28).…”
Section: Highly Active Antiretroviral Therapy (Haart) Is Effective Atmentioning
confidence: 99%